All Flesh Must Be Eaten : análise simbólica do fenômeno zumbi - Guimarães, Luciana Guerrieri Barbosa Viana (2014)
The research aimed at understanding the motivational factor of registered people participating in the virtual community Zombie walk Rio de Janeiro, placed in the social network website Facebook. Therefore, a survey was applied to men and women with age over 18 (eighteen) years old, registered in the above mentioned community. The survey had 6 (six) identification questions and 6 (six) semi-open questions answered by the internet. To analyze the data, it was used the Thematic Analysis, described by author Douglas Ezzy (2002). From the gathered data, a profile of the zombie character was defined and its context from the Jungian psychology point of view. It was observed that the zombie character represents a metaphor for current constellated complexes associated to feelings of strangeness, bond break, lack of solidarity, existential insecurity, relationship dehumanization, consumerism and fear or denial of death. The conclusion from the analysis of the character is a reflection of the current life panorama in society and relationships, as well as a projection of individual anxieties